Kepemimpinan Perempuan Dalam Islam: Perspektif Hadits Sebagai Sumber Rujukan - Mubarok, Ramdanil (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2023)
Women's leadership in the public sphere is an interesting discussion. This article takes an inventory of the hadiths about women's leadership thematically (maudhu'i), describes the quality of the sanad and its matrices through takhrij hadith, and analyzes its content using a textual and contextual approach. The results show that there are 20 hadiths about women's leadership spread over five standard hadith books, namely Sahih Bukhari, Sahih Muslim, Sunan Abu Daud, Sunan Tirmidhi, Sunan Nasa'i, and Musnad Ahmad. Analysis of the quality of the sanad and matan hadiths that have been inventoried shows that all of them meet the qualifications of authenticity. The meaning contained in the hadiths about women's leadership is divided into two categories, namely the category of not allowing a woman to be a leader and the category of allowing a woman to be a leader with their respective arguments. If understood textually, then women are prohibited from being leaders, but if understood contextually then there is no prohibition for a woman to become a leader in the public sphere.